A new era for African health systems: Market shaping and the African Continental Free Trade Area (AfCFTA) - Jonta Kamara; Ukeme Essien; Alain Labrique (Public Health Challenges, 2024)
Abstract The COVID‐19 pandemic has forced a reflection on the origins of supplies in African healthcare market and underscored the need for an increase in local manufacturing of medical supplies. Several African countries’ health markets have been heavily reliant on imports. First, this article demonstrates how the African healthcare market has had a high import dependency and the role that the African Continental Free Trade Area (AfCFTA) could play to reverse this. It is estimated that African countries import between 80% and 94% of medical supplies, 75% of testing kits, between 70% and 95% of pharmaceuticals, and 99% of vaccines. Second, during the COVID‐19 pandemic, countries imposed export restrictions which impacted the flow of medical supplies to African countries. This finding highlighted the limited production capabilities on the African continent and reiterated the need to strengthen continental value chains and local manufacturing capacity to establish the continent's New Public Health Order. Third, there was the emergence of local innovations seeking to minimize the impact of these supply chain disruptions. Using case studies on the local production of COVID‐19 testing kits and personal protective equipment, the article highlights progress made toward health market reform. It calls attention to the implementation of the AfCFTA to strengthen the supply, manufacturing, and trade of medical resources. Fourth, this article highlights countries that have African‐made pharmaceuticals and vaccinations and the importance of regional hubs to expand these products in African healthcare markets. It concludes by discussing investments made to expand local manufacturing of health products.